Global sourcing of complex production processes - Christian Schwarz; Jens Suedekum (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
We develop a theory of a firm in an incomplete contracts environment which decides on the complexity, the organization, and the global scale of its production process. Specifically, the firm decides i) how many intermediate inputs are simultaneously combined to a final product, ii) if the supplier of each input is an external contractor or an integrated affiliate, and iii) if that input is offshored to a foreign country. Our model leads to a rich set of predictions on the internal structure of multinational firms. In particular, it provides an explanation why many firms choose hybrid sourcing and have both outsourced and integrated suppliers.
Keywords: F12; D23; L23; 330; multinational firms; outsourcing; intra-firm trade; offshoring; vertical FDI